KLASIFIKASI DAERAH TERCEMAR LIMBAH ACID SLUDGE MENGGUNAKAN METODE SPECTRAL MIXTURE ANALYSIS BERBASIS DATA LANDSAT 8 - Haryani, Nanik Suryo; Sulma, Sayidah; Pasaribu, Junita Monika; Fitriana, Hana Listi (Institut Teknologi Sepuluh Nopember, 2015)
The existence waste materials in an area potentially triggers the contamination, and in turns will damages the environment particularly in the vicinity of waste disposal location. This research is aimed to analyze the acid sludge waste contaminated area using the remote sensing satellite Landsat 8. The applied methodology for analyzing the spectral of contaminated area is using spectral mixture analysis method. The result shows that the spectral analysis using this method with spectral reference based on endmember images convey the better output. This is caused by the availability of the SWIR wave length in Landsat 8. The SWIR wave length is sensitive against a highly contaminated substance like as sand and sludge, and contributes to non land contaminated substance like vegetation. Further the index classification based on images endmember shows the result which matching better to the field condition. Based on accuracy review, the result shows the classification accuracy based on this index as 62.5 %.